The The social currency of 'tíquete feira' as a public policy promoting human dignity for rural families in situations of vulnerability (REMUNOM, 2024)
The fair ticket in Brazilian municipalities is implemented through public policies aimed at greater appreciation of family farming activities and to foster rural production while assisting families in situations of socioeconomic vulnerability. Small rural producers require policies that facilitate the sale of their products. Would the implementation of the fair ticket be sufficient to solve the dilemmas faced in family farming? The objective of the research is to address studies that can serve as a basis for analyzing the fair ticket as a means to promote local commerce and reduce social inequalities in rural areas. The methodological approach will be conducted through a literature review, based on descriptive and exploratory analysis, focusing on produced knowledge and findings. It aims to demonstrate the necessary applications of fair ticket public policies to alleviate social inequality issues and point out the necessary implementation of actions that can contribute to strengthening the dignity of rural families in vulnerable situations. This will result in a strengthened inclusion of family farming with conditions to achieve satisfactory economic development results in an inclusive food production logic, within an entrepreneurial and solidarity-based framework.